80.9k views
5 votes
Y=x-4 y=4x+2
whats the solution of system equations

User JVMATL
by
5.0k points

1 Answer

4 votes

Answer:

X=-2

Y=-6

Explanation:

Since both equations are already expressed in the simplest form of y, then we equate them to be equal hence

x-4=4x+2

Bringing like terms together

-4-2=4x-x

Solving both sides

-6=3x

Making x the subject then

X=-6/3=-2

Subsrituting the value of x into any of the initial equations

Y=x-4 then y=-2-4=-6

Therefore, the solution is

X=-2

Y=-6

User Souvik
by
5.2k points